Lockdowny i ich zasadność w kontekście filozofii ekonomicznej Adama Smitha i liberalizmu - Żurawski, Paweł (Annales. Etyka w Życiu Gospodarczym, 2020)
Since the beginning of 2020, lockdowns have been introduced in numerous countries across the world in response to the emergence of coronavirus SARS-CoV-2 that causes the COVID-19 disease. Although the topic of lockdowns has been considered from numerous perspectives, it has not yet been analyzed in the context of Adam Smith’s economic philosophy and liberalism. This paper aims to list – at least to some extent, as the topic is very broad – the most prominent arguments that have arisen in the worldwide discussion on the effectiveness and side effects of lockdowns. In addition, the work provides some elements of Smith’s economic philosophy and liberalism. Finally, the arguments that have arisen in the academic discussion since the introduction of lockdowns are analyzed, and the legitimacy of lockdowns is assessed in the context of Smith’s principles. The methods used for the analysis are text exegesis and rational reconstruction. As far as the conclusions are concerned, an explicit assessment of the legitimacy of lockdowns in the discussed context is considered impossible, although for many elements of Smith’s liberalism, lockdowns are not legitimate at all.